Offshore Technology Conference 1983
DOI: 10.4043/4465-ms
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Offshore Sampling and Testing on Undrained Soil Shear Strength

Abstract: The empirical procedures for offshore foundations design are directly influenced by the shear strength values selected for analyses.There is generally a large amount of scatter in measured undrained shear strength data from offshore borings because of various types of laboratory tests and sample disturbance. A comparison of strength data obtained on samples of cohesive soils from the Gulf of Mexico taken with a 2.25-in.-OD thin-wall tube percussion sampler and a 3.0-in.-OD thin-wall push sampler confirms that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 2 publications
1
6
0
Order By: Relevance
“…Thus, the study supported earlier results by Olson and Dennis (1982) and Young et al (1983), that recommended the empirical procedures used for axially loaded pile design be based on strengths determined from UUP on 3 inch (.076 m) diameter or larger high quality pushed samples. The study confirmed that a conservative bias could be avoided by interpreting the design Su from UUP or miniature vane tests on pushed samples (MVP) as opposed to unconfined compression tests on driven samples (UCD).…”
Section: Reliability Of Various Design Methodssupporting
confidence: 86%
See 1 more Smart Citation
“…Thus, the study supported earlier results by Olson and Dennis (1982) and Young et al (1983), that recommended the empirical procedures used for axially loaded pile design be based on strengths determined from UUP on 3 inch (.076 m) diameter or larger high quality pushed samples. The study confirmed that a conservative bias could be avoided by interpreting the design Su from UUP or miniature vane tests on pushed samples (MVP) as opposed to unconfined compression tests on driven samples (UCD).…”
Section: Reliability Of Various Design Methodssupporting
confidence: 86%
“…OtTshore soil samples, especially if obtained by wireline percussion techniques, are known to be adversely affected by sample disturbance, as shown by Erruich (1971), Quiros et al (1983) and Young et al (1983). This problem is exacerbated at deep water sites where the samples are subjected to large hydrostatic stress relief prior to laboratory testing.…”
Section: $Anmle Disturbance and Shear Strength Determinationmentioning
confidence: 99%
“…Additional coring effects result from the rotational coring tool [ Arman and McManis , 1977; Young et al , 1983]. Figure 9 shows evidence of striation from the cutting shoe in 2‐D X‐rays and 3‐D tomograms of 10B‐5R and 10B‐14R core samples recovered using the rotary cutting method (i.e., Hyace Rotary Core).…”
Section: Discussionmentioning
confidence: 99%
“…Reduction of the effective stresses by this mechanism (Okumura 1971;Procter 1976;Young et al 1983), or by drainage of the sample during storage and testing (Adams and Radhakrishna 197 1 ;Kirkpatrick and Khan 1984), causes significant loss of strength: Proportionally larger changes are observed in stress-strain properties such as modulus or pore-water pressure parameters.…”
Section: Reviewmentioning
confidence: 97%